2008
DOI: 10.1002/prca.200780153
|View full text |Cite
|
Sign up to set email alerts
|

The urine proteome as a biomarker of radiation injury

Abstract: Terrorist attacks or nuclear accidents could expose large numbers of people to ionizing radiation, and early biomarkers of radiation injury would be critical for triage, treatment and follow-up of such individuals. However, no such biomarkers have yet been proven to exist. We tested the potential of high throughput proteomics to identify protein biomarkers of radiation injury after total body X-ray irradiation in a rat model. Subtle functional changes in the kidney are suggested by an increased glomerular perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
(34 reference statements)
4
18
0
Order By: Relevance
“…As a result, pathological changes in human organs that may be reflected in the blood plasma/serum may also be reflected and detected in the urinary proteome (Gonzalez-Buitrago et al 2007). In fact, the work presented here was inspired by a recent study by Sharma et al, where a total body X-ray irradiation (10 Gy) of rats showed a decrease in urinary excretion of albumin and immunoglobulins, but with a concomitant increase in alpha-1-acid glycoprotein (Sharma et al 2008). It was therefore interesting to investigate whether internal exposure from an alpha emitter produced similar changes to the expression of urinary protein biomarkers that could potentially be utilized as a screening tool for triaging an internal contamination in an R/N emergency.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…As a result, pathological changes in human organs that may be reflected in the blood plasma/serum may also be reflected and detected in the urinary proteome (Gonzalez-Buitrago et al 2007). In fact, the work presented here was inspired by a recent study by Sharma et al, where a total body X-ray irradiation (10 Gy) of rats showed a decrease in urinary excretion of albumin and immunoglobulins, but with a concomitant increase in alpha-1-acid glycoprotein (Sharma et al 2008). It was therefore interesting to investigate whether internal exposure from an alpha emitter produced similar changes to the expression of urinary protein biomarkers that could potentially be utilized as a screening tool for triaging an internal contamination in an R/N emergency.…”
Section: Discussionmentioning
confidence: 79%
“…There has been a renewed interest in studying urinary biomarkers to be used as a rapid screening tool for IR exposure in an R/N emergency. However, most of the recent studies have been focused on exposure to external radiation, such as gamma radiation (Lanz et al 2009;Tyburski et al 2009a, b;Johnson et al 2011Johnson et al , 2012) and X-rays (Sharma et al 2008(Sharma et al , 2010. The present study aims to investigate some urinary proteins as a possible clinical biomarker for internal exposure.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Conversely, analysis of proteins from blood or urine will reflect the health not only of an organ (e.g., the health of the liver by measuring the activity of the blood transaminases) but also of the whole organism. 22,[25][26][27][28][29][30][31][32][33] Although a particular secreted molecule (and/or protein) may reveal information about a particular organ, a combination of secreted molecules (and/or proteins) may reflect the physiological state of a particular cell type, or of an organ or of the whole organism. Here we primarily discuss secreted proteins, as analyzed by mass spectrometry.…”
Section: Secretome: Definition and Classificationmentioning
confidence: 99%
“…[1][2][3][4][5][6]8 Secretomes may be classified according to various criteria, such as the type of the cell or the type of the tissue producing the secretome, or the location of the secreted proteins such as extracellular but nonsystemic, intraorgan (e.g., intrahepatic) or extracellular but systemic, extraorgan (e.g., blood, saliva, urine, or lymphatic fluid). [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Depending on the type of secretome analyzed, specific information may be obtained. For example, analysis of proteins secreted by cells grown in cell culture will reflect the health and activity of those cells.…”
Section: Secretome: Definition and Classificationmentioning
confidence: 99%